Study of the behaviour of reinforced masonry wallets subjected to diagonal compression through numerical modelling - Haach, V. G. (2014)
Shear walls are subjected to flexure and shear efforts in conjunction with compressive stresses associated to the gravity loads. In shear mode, diagonal cracks develop at the unit-mortar interface or both at the unit-mortar interface and through units as result of a biaxial tension-compression stress state, which in unreinforced masonry generally mean the collapse. The brittle failures of unreinforced masonry shear walls, which are more remarkable with high axial loads, may be prevented by the use of steel reinforcement. Diagonal compression tests allow obtaining a good prediction of the tensile strength of masonry walls in this biaxial tension-compression stress state. This paper aims to study the behaviour of reinforced masonry in diagonal compression tests through numerical modelling. A series of diagonal compression tests carried out on concrete block masonry with distinct types of reinforcement’s arrangements are modelled using the software DIANA®. Results indicate that horizontal and vertical reinforcements applied in conjunct provide an increase on the shear strength and ductility. On the other hand, the application of horizontal reinforcements alone leads only to an increase of ductility.